Morphological redescription of Culex (Microculex) davisi and Cx. (Mcx.) imitator (Diptera: Culicidae) including structures and stages not previously described - Bangher, Debora Natalia; Stein, Marina (Zootaxa, 2017)
The adults, male genitalia and fourth-instar larva of Culex (Microculex) imitator Theobald and Culex (Microculex) davisi Kumm, and the pupa of the latter species, are re-described. The female genitalia of both species and the pupa of Culex (Microculex) imitator are described for the first time. Information on distribution, bionomics and taxonomy is also included.